Le sujet en Islam - Christian Capapé; Christian Reynaud (Éducation et Socialisation)
In Islam, the subject, is considered as totally submited to God’s will, whose message was revealed worldwide by the Prophet Muhammad, and its inviolable norms must be strictly respected. These norms are exclusively dogmatic and constitute the islamic law or ‘Shariah.’ However, some muslim thinkers such as Ali Merad, Mohamed Arkoun and Malek Chebel try to show that it exists in Islam principles of right that offer to muslim subject larger freedom areas, avoiding fundamentalism and accepting a more liberal position. They suggest a diachronic reading of Coran, closely related to the most significant aims of Revelation and to subject ontology; including Islam in a modern way of life, without changing its essence. Abdennour Badir suggests a ‘self islam’ in which the Muslim subject is free and without any complexes.